SPE Annual Technical Conference and Exhibition 1995
DOI: 10.2118/30451-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Extended Reach Drilling – An Eye to 10 km Stepout

Abstract: SPE Members Abstract This paper will present recent technological innovations which have been used to surpass previous extended reach records together with other technologies which are viewed as fundamental in overcoming current limitations for extended reach and designer wells. The paper will focus on three specific drilling applications which provide a range of options for operating companies with varying field development philosophies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since its inception, flotation technology has allowed operators to extend wells in excess of 12,000 ft, and presently 30,000 ft offsets are being considered (Ryan and Raitt 1995). Other operators have successfully used such techniques in fields around the world.…”
Section: Fig 2-illustration Of How Friction and Deviation Work Togetmentioning
confidence: 99%
“…Since its inception, flotation technology has allowed operators to extend wells in excess of 12,000 ft, and presently 30,000 ft offsets are being considered (Ryan and Raitt 1995). Other operators have successfully used such techniques in fields around the world.…”
Section: Fig 2-illustration Of How Friction and Deviation Work Togetmentioning
confidence: 99%
“…This increased in the 1990s, and one targeted 10 km as a likely step out. Ryan et. al (1995) conducted a review of technology in 1995 and concluded that 10 km step out is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Extended Reach Drilling (ERD) is a technique to drill directional/horizontal wells beyond the routine capabilities of drilling rigs and tools. ERD was initiated in 1980's and rapidly evolved during the 1990's [1][2][3][4]. Naegel et al [5] reported an ERD well with a 20,341.2 ft horizontal departure at 5,577 ft true vertical depth (TVD).…”
Section: Introductionmentioning
confidence: 99%